Children's perspectives on vegetable consumption and gardening: outcomes from a qualitative study in Kuala Lumpur, Malaysia - Mok, Kai Ting; Tung, Serene En Hui; Kaur, Satvinder; Chin, Yit Siew; Mohammad Yusoff, Martini; Ulaganathan, Vaidehi (Wiley, 2024)
Urban poor children have low vegetable consumption due to food insecurities leading to limited access to vegetables. Children's involvement in gardening may improve their vegetable consumption and connection with nature. This qualitative study explored the potential facilitators and barriers related to vegetable consumption and gardening among urban poor children in Kuala Lumpur, Malaysia. Four focus group discussions were conducted among 20 randomly selected children aged 9–12 years, residing in selected low-cost flats in Kuala Lumpur, Malaysia, from November 2021 to January 2022. Thematic analysis via NVivo software was conducted to analyse the transcripts. Children reported several barriers to eating vegetables, such as disliking taste, sensory and appearance, limited accessibility and vegetable availability at home. Most children felt positive and interested to join gardening. The findings are useful in planning nutrition intervention programmes that incorporate gardening as one of the elements to improve vegetable consumption.